Antibiotic resistance in uropathogens across northern Australia 2007–20 and impact on treatment guidelines. Issue 3 (14th August 2021) - Cuningham, Will; Perera, Shalinie; Coulter, Sonali; Nimmo, Graeme R; Yarwood, Trent; Tong, Steven Y C; Wozniak, Teresa M
Abstract: Background: Urinary tract infections are common and are increasingly resistant to antibiotic therapy. Northern Australia is a sparsely populated region with limited access to healthcare, a relatively high burden of disease, a substantial regional and remote population, and high rates of antibiotic resistance in skin pathogens. Objectives: To explore trends in antibiotic resistance for common uropathogens Escherichia coli and Klebsiella pneumoniae in northern Australia, and how these relate to current treatment guidelines in the community and hospital settings. Methods: We used data from an antibiotic resistance surveillance system. We calculated the monthly and yearly percentage of isolates that were resistant in each antibiotic class, by bacterium. We analysed resistance proportions geographically and temporally, stratifying by healthcare setting. Using simple linear regression, we investigated longitudinal trends in monthly resistance proportions and correlation between community and hospital isolates. Results: Our analysis included 177 223 urinary isolates from four pathology providers between 2007 and 2020. Resistance to most studied antibiotics remained <20% (for E. coli and K. pneumoniae, respectively, in 2019: amoxicillin/clavulanate 16%, 5%; cefazolin 17%, 8%; nitrofurantoin 1%, 31%; trimethoprim 36%, 17%; gentamicin 7%, 2%; extended-spectrum cephalosporins 8%, 5%), but many are increasing by 1%–3% (absolute) per year. Patterns of resistance were similar between isolates from community and hospital patients. Conclusions: Antibiotic resistance in uropathogens is increasing in northern Australia, but treatment guidelines generally remain appropriate for empirical therapy of patients with suspected infection (except trimethoprim in some settings). Our findings demonstrate the importance of local surveillance data (HOTspots) to inform clinical decision making and guidelines.